Chapter 3 PHYLOGEOGRAPHY OF SOUTHERN HEMISPHERE BLUE MUSSELS OF THE GENUS MYTILUS: EVOLUTION, BIOSECURITY, AQUACULTURE AND FOOD LABELLING - JONATHAN P. A. GARDNER; PABLO A. OYARZÚN; JORGE E. TORO; ROMAN WENNE; MALGORZATA ZBAWICKA (Taylor & Francis, 2021)
oceanography, climate change, reefs, marine science, marine conservation, marine research
English[eng]
Keywords: bic Book Industry Communication; bic Book Industry Communication; bic Book Industry Communication; bic Book Industry Communication; bic Book Industry Communication; bic Book Industry Communication; bic Book Industry Communication; bic Book Industry Communication; bic Book Industry Communication; bic Book Industry Communication; oceanography, climate change, reefs, marine science, marine conservation, marine research